Why Many Indonesians Are Underproductive - Dendy Sandra; Tarigan , Heskeyel Pranata (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
Productivity is one of the key indicators in measuring a nation’s progress. Despite Indonesia's demographic advantage, data shows that the productivity level of its citizens remains low compared to other Southeast Asian countries. This study aims to identify the main factors contributing to low productivity in Indonesia using a descriptive qualitative approach through literature review. The data was collected from 15 national scientific journals discussing issues related to work culture, financial and digital literacy, time management, quality of education and training, and government policies. The findings reveal that low productivity is caused by a combination of structural and cultural factors, such as undisciplined work behavior, poor time management, limited work skills, and the lack of comprehensive policies supporting human resource development. The lack of integration between education, vocational training, and industrial needs further exacerbates the productivity gap. Therefore, improving productivity requires a collaborative cross-sectoral approach, including the formation of a productive work culture, strengthening literacy, reforming educational policies, and enhancing infrastructure support. This study is expected to serve as a reference for academics, policymakers, and industry stakeholders in formulating sustainable and contextual national productivity enhancement strategies.